A simple procedure for the purification of active fractions in aqueous extracts of plants with allelopathic properties - Borghetti, Fabian (2013)
Most studies conducted to test the allelopathic activity of plant parts have made use of water as solvent. However, the presence of polar, water-soluble substances, such as proteins and carbohydrates, tends to hamper the purifi cation of active compounds. In this study, we present a simple purifi cation procedure that separates the active fraction of the extract from the undesirable substances, thus facilitating the search for active molecules through standard chromatographic methods. Aqueous leaf extracts of three Cerrado species (Caryocar brasiliense, Qualea parvifl ora and Eugenia dysenterica) were prepared at 5% concentration (w/v) and stored at 4°C (crude extracts). Aft er 24 h, these solutions were fi ltered and freeze-dried. Th e powder obtained was dissolved in methanol, fi ltered again, evaporated and dissolved in water for bioassays (purifi ed extracts). For the bioassays, seedlings of Sesamum indicum were grown for fi ve days in aqueous solutions prepared from crude and purifi ed extracts at concentrations ranging from 0.1% to 1.0% (w/v). Seedling growth in distilled water was set as a control. In comparison with the control, we found that test solutions prepared from both crude and purifi ed extracts signifi cantly inhibited sesame seedling growth. However, solutions prepared from purifi ed extracts were two to ten times more inhibitory to seedling growth than were those prepared from crude extracts. Th e inhibition of root growth ranged from 35% to 77%, depending on the plant species, at a concentration as low as 0.1%. Roots were more aff ected than were shoots. Th e eff ects of purifi ed extracts on seedling morphology were similar to those observed when crude extracts were employed, indicating that the procedure of purifi cation of crude extracts did not interfere with the mode of action of the active substances.